2016
DOI: 10.2147/ott.s100164
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed had significantly better clinical efficacy in patients with stage IV lung adenocarcinoma with susceptible EGFR mutations receiving platinum-based chemotherapy after developing resistance to the first-line gefitinib treatment

Abstract: BackgroundIncreased evidences show that epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors such as gefitinib could prolong progression-free survival (PFS) compared with cytotoxic chemotherapy for metastatic lung nonsquamous cell carcinoma harboring susceptible EGFR mutation, and gefitinib was served as the first-line therapy. However, acquired resistance is inevitable, but the salvage therapies are still unclear.Patients and methodsWe designed a retrospective study of the salvage therapy and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…Because the efficacy of continuous EGFR‐TKI monotherapy is relatively moderate, many studies have evaluated the efficacy of EGFR‐TKIs combined with other agents, such as chemotherapy, antiangiogenic drugs, or monoclonal antibodies. In the real world, many patients receive pemetrexed plus platinum chemotherapy and achieve PFS of 4.9–5.4 months and OS of 16.1–19.5 months after they develop symptomatic resistance to EGFR‐TKI treatment . The IMPRESS study showed that continuing gefitinib and chemotherapy (cisplatin plus pemetrexed) did not prolong the median PFS (5.4 months in both groups) and was also detrimental to the median OS (13.4 vs. 19.5 months, HR 1.44, 95% CI 1.07–1.94; P = 0.16) compared to the placebo plus chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the efficacy of continuous EGFR‐TKI monotherapy is relatively moderate, many studies have evaluated the efficacy of EGFR‐TKIs combined with other agents, such as chemotherapy, antiangiogenic drugs, or monoclonal antibodies. In the real world, many patients receive pemetrexed plus platinum chemotherapy and achieve PFS of 4.9–5.4 months and OS of 16.1–19.5 months after they develop symptomatic resistance to EGFR‐TKI treatment . The IMPRESS study showed that continuing gefitinib and chemotherapy (cisplatin plus pemetrexed) did not prolong the median PFS (5.4 months in both groups) and was also detrimental to the median OS (13.4 vs. 19.5 months, HR 1.44, 95% CI 1.07–1.94; P = 0.16) compared to the placebo plus chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the real world, many patients receive pemetrexed plus platinum chemotherapy and achieve PFS of 4.9-5.4 months and OS of 16.1-19.5 months after they develop symptomatic resistance to EGFR-TKI treatment. 26,27 The IMPRESS study showed that continuing gefitinib and chemotherapy (cisplatin plus pemetrexed) did not prolong the median PFS (5.4 months in both groups) and was also detrimental to the median OS (13.4 vs. 19.5 months, HR 1.44, 95% CI 1.07-1.94; P = 0.16) compared to the placebo plus chemotherapy. Nearly 5% of patients in the IMPRESS study experienced grade 3 or worse AEs, including anemia and neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, pemetrexed has less side effects than other TKIs and a RCT has also proven it to be effective as maintenance therapy after first-line PCT in non-squamous NSCLC 23. Also, as a second-line, pemetrexed had significantly better clinical efficacy in patients with susceptible EGFR mutations after progression of first-line TKI 24. However, except for Sequist et al’s study, the other eight studies did not use pemetrexed in first-line treatment in order for us to compare TKIs in our analysis, due to the fact that pemetrexed was approved as first-line treatment by FDA in 2009 10…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not available due to the financial problem. We selected the pemetrexed as a second-line therapy as pemetrexed has been known to be an effective option for patients with NSCLC harboring sensitive EGFR mutation after gefitinib failure in retrospective studies (16,17).…”
Section: Discussionmentioning
confidence: 99%